Understanding Intimate Partner Cyber Abuse across Partnership Categories Based on Gender Identity and Sexual Orientation. Issue 1 (2nd January 2023) - Butler, Leah C.; Fissel, Erica R.; Gildea, Brian; Fisher, Bonnie S.
ABSTRACT: Research indicates non-cisgender and non-heterosexual individuals experience higher rates of intimate partner violence compared to their cisgender and heterosexual counterparts. It is unknown if this is the case for intimate partner cyber abuse (IPCA). Thus, the current study examines IPCA prevalence rates among a sample of adults in intimate partnerships and compares these rates across four partnership categories, defined by gender identity and sexual orientation. We also assess prevalence rates within five IPCA domains and patterns of recurring victimization. Findings suggest victimization experiences may differ across partnership categories and highlight the need for further research with non-heterosexual and non-cisgender populations.